Enforcement of the Mediation Settlement in Georgia - Guram Barnabishvili; Sophiko Tsiklauri (Alternative Dispute Resolution Yearbook, 2017)
The present article reviews the various types of the mediation like court mediation, notary mediation and private mediation and their enforcement mechanisms according to the existing laws and as of the anticipated alterations in the existing legislation of Georgia. At this crucial moment of commencement of judicial regulation of the mediation in Georgia, some recommendations relying on the practices, notary acts, doctrines and researches of the United States, EU countries including the post-Soviet Union countries, are already drafted. The article points out, what may at the first glance seem as a minor issue - the significance of the judicial regulation of the enforcements of the mediation settlements, its role in a prevention of the infringement of the mediation settlement by the parties and growing reliance of society towards the mediation, as a mean of alternative dispute resolution.